The European Grief Conference, Copenhagen 2022: An effort to unite the field of bereavement care in Europe. - Müller, H.; Zsak, E.; O'Connor, M.; Keegan, O.; Graven Østergaard, T.; Holm Larsen, L. (Death Studies, 2025)
Bereavement care in Europe varies in quality and availability. Through greater collaboration across Europe, there could potentially be an opportunity to improve care. This article discusses the inaugural European Grief Conference held in Denmark in 2022: "Bereavement and Grief in Europe – Emerging Perspectives & Collaborations". The conference was structured around a 4-tiered public health model of bereavement care needs. It included practice, research, policy, and educational perspectives. A total of 250 people from 27 different countries participated. To determine if the conference had appealed to a broad European audience of grief professionals and to assess how the conference was received by participants, we examined registration/submission data, the results of a one-word real-time feedback exercise, and the answers to an online satisfaction survey. The results indicated wide interest in greater information sharing and collaboration across Europe among bereavement care, research, and education professionals.